EVALUATION THE ABILITY OF TITANUM OXIDE NANOPARTICLES TO INCREASE THE PRODUCTION OF PRODIGIOSIN AND PHENASINE FROM Serratia marcescens AND Pseudomonas aeruginosa RESPECTIVELY - Yaaqoob, L. A.; Abed, R. M.; Kamona, Z. K.; Altaee, M. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was aimed to investigate the possibility of titanium oxide nanoparticles to enhance the production of both prodigiosin by Serratia marcescens and phenazine by Pseudomonas aeruginosa. Moreover; the poor non-selective nutrient broth was used instead of using the selective nutrient broth for the production of both compounds to reduce the economic cost for production. Different concentrations of titanium oxide nanoparticles (0.005, 0.01, 0.015 mg/L) were used in this study to choose the most suitable concentrations to increase production. Both prodigiosin and phenazine were considered promising drugs for treating many diseases owing to their characteristics of antibacterial, antifungal, immunosuppressive, and anticancer activities. The results revealed that both the prodigiosin and phenazine production was increased from S. marcescens and Pseudomonas aeruginosa when using titanium oxide nanoparticles at (0.01 mg/L) concentration and the size of an average diameter was 57.07 nm.